Antibodies to the Vi capsule of Salmonella Typhi in the serum of typhoid patients and healthy control subjects from a typhoid endemic region - Deborah House; Vo A. Ho; To S. Diep; Nguyen T. Chinh; Phan V. Bay; Ha Vinh; Minh Duc; Christopher M. Parry; Gordon Dougan; Nicholas J. White; Jeremy J. Farrar; Tran Tinh Hien; et al. (Journal of Infection in Developing Countries)
Background: There is very little published data on the antibody response to the Vi capsular polysaccharide (Vi-CPS) of S. Typhi during naturally acquired typhoid fever in an endemic area. Methodology: An indirect ELISA, using tyraminated, purified Vi-CPS, was used to assay anti-Vi-CPS antibodies from typhoid fever cases and controls living in the Ho Chi Minh City and Mekong Delta region of Viet Nam. Results: Antibody response to Vi-CPS is significantly higher in typhoid patients who have been ill for more than two weeks than those who are in the first two weeks of illness. The anti-Vi-CPS response is similar for adults and children. Anti-Vi-CPS antibodies can be detected in the sera of non-typhoid patients. The frequency with which this occurs increases with age, probably reflecting increased exposure to S. Typhi. Conclusions: Anti-Vi_CPS is elicited in persons infected with S. Typhi but only after a prolonged duration of illness. Vaccine trials have shown anti-Vi-CPS antibodies to be protective; thus early treatment of typhoid patients, i.e. in the first two week of illness before the Vi-CPS response is elicited, may inhibit the development of this protective immune response.